Sole Family Survivors: Older Adults Lacking Family of Origin Kin. (30th December 2021) - Brown, Susan L; Mellencamp, Kagan A; Lin, I-Fen
Abstract: Objectives: We introduced a unique form of kinlessness: sole family survivorship, which describes the lack of family of origin (i.e., biological parents and siblings) kin. This form of kinlessness may be particularly consequential for older adults who experience other forms of kinlessness (e.g., no spouse/partner or no children) as they are especially likely to have relied on their family of origin for support. Methods: Data from the 1998–2014 Health and Retirement Study ( N = 148, 346 person-waves) were used to estimate the prevalence of sole family survivorship among adults aged 55 and older and men and women aged 55–74 and 75+. Variation in prevalence levels of sole family survivorship across sociodemographic characteristics, health indicators, and family factors were also estimated. Finally, we tracked cohort trends in sole family survivorship. Results: More than 1 in 10 adults aged 55+ were sole family survivors and this figure rose to more than 1 in 4 among those aged 75+. Adults with no spouse/partner and no children were especially likely to be sole family survivors, meaning they face a double burden of kinlessness. Discussion: Sole family survivorship represents the culmination of loss of multiple, lifelong kin ties. It is more common among those lacking other close kin, signaling the presence of a uniquely vulnerable group of older adults who experience multiple forms of kinlessness. Future research should address how older adults and society at large adapt to kinlessness to ensure successful aging.